Effects of Remotely Supervised Physical Activity on Health Profile in Frail Older Adults: A Randomized Controlled Trial Protocol - Zhang, Xin; Li, Jinwei; Sui, Xin; Xu, Linqi; Zhu, Lanyu; Pang, Yue; Yu, Tianzhuo; Lian, Xiaoqian; Yu, Tianyue; Li, Yuewei; Xu, Haiyan; Li, Feng (Frontiers in Aging Neuroscience, 2022)
Background: Frailty is considered a major public health challenge of the 21st century, characterized by the decline of multiform body functions. Physical activity may be the most effective intervention to delay frailty. This study aims to verify the effect of remotely supervised physical activity on health profile in community-dwelling frail older adults. Design: We will perform a multicenter, three-blind, two-arm, cohort randomized controlled study. Methods: The intelligent exercise rehabilitation management system (IERMS) is an integrated digital platform which involving evaluation, guidance, monitoring and feedback. A total of 120 participants aged ≥65 years and diagnosed as frailty on FRAIL scale will be recruited, randomly divided into two groups. Group 1 will receive 12-week IERMS-based intervention, Group 2 will receive usual care. Data will be collected at baseline, 12 weeks, and 24 weeks. Primary outcome is physical function, secondary outcomes include gait parameters, psychology and cognition measurement. Analyses will be performed using DSS statistics, version 25, P< 0.05 will be considered statistically significant. Conclusions and Implications: We believe that intervention will play a positive role in delaying the frailty. If our program is effective, we will provide a viable means to promote healthy ageing in primary health care.